Sosialisasi Perbaikan Metode Kerja Dengan Prinsip 5S Berdasarkan Identifikasi Hazard Di CV. Epen Garage X Azizskip - Tri Novita Sari; Masri Pradipto; Sri Hartini (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2021)
Occupational Safety and Health (OSH) is a safe and healthy condition when doing work. This safe and healthy condition are useful for both workers, companies or organizations and for the environment around the workplace. OSH is an important aspect in workshop, including CV. Epen Garage X Azizskip which is a motorbike repair workshop located in Citeuteup area, Bogor City, West Java. OSH will be created if there is no potential danger or hazard, therefore it is necessary to identify hazards in the workshop. This study aims to identify hazards using Hazard and Operability Study (HAZOP) method and work improvement using Seiri, Seiton, Seiso, Seiketsu dan Shitsuke (5S) method. The types of hazards, risk levels and sources of hazards will be identified by the HAZOP method. Generally the hazards in the workshop are because workers do not use Personal Protective Equipment (PPE) such as work clothes, gloves, safety shoes, safety goggles and also messy workshop condition. After identifying the types of hazards, a work improvement method is needed to prevent accidents in workshop, using the 5S method.